(untitled) (Faridpur Medical College Journal, 2019)
Polycystic Ovarian Syndrome (PCOS) is the most common endocrine disorder responsible for subfertility in young women. The aim of the study was to compare the efficacy of Letrozole over Clomiphene citrate (CC) for ovulation induction in patients with PCOS. It was a prospective randomized trial in a private practice setting. The study period was 3 years, which includes 240 sub fertile patients with PCOS. Patients were divided into two groups. Group-A: 120 patients got Letrozole (2.5 mg) tab, 2 tabs once daily from D2-D6 for 3 cycles. Group-B: 120 patients took tab. Clomiphene citrate (50mg), 2 tabs once daily from D2-D6 for 3 cycles. Trans-vaginal ultrasound was done on D12-D13 to document number of follicles, measurement of dominant follicle and endometrial thickness. Ovulation and pregnancy rate was measured. Results showed that Letrozole have significantly better effect on endometrial thickness (Let 9.2 mm vs CC 8.1mm) and pregnancy rate (Let 44% vs CC 24%). In CC, multiple follicles were found (CC 44% vs Let 30%). Ovulation occurred in 65% with Letrozole group and 64% in CC group without a significant statistical difference. The study concluded that Letrozole have better effect for induction of ovulation in PCOS patient in comparison to CC. Faridpur Med. Coll. J. Jul 2018;13(2): 78-81